The Influence of the ICT- Based Inquiry Based Learning Model on Students' Critical Thinking Skills: Meta-analysis - Asrul Sani; Miftachul Amri; Yosep Heristyo Endro Buruno; Venty Sopacua; Muhammad Lutfi; Tomi a Santosa (Universitas Muhammadiyah Enrekang, 2024)
The purpose of this study was to determine the effect of ICT-based inquiry-based learning model on students' critical thinking skills. This research is a type of quantitative research with a meta-analysis approach. The data in this study came from the analysis of 16 national journals published in 2020-2024. The inclusion criteria in this meta-analysis consisted of experimental or quasi-experimental method research, data derived from SINTA and Scopus indexed journals or proceedings, research related to ICT-based inquiry-based learning models on students' critical thinking skills, sample size> 25 students; Data obtained from trusted databases, namely sciencedirect, ERIC, Wiley and Taylor of Francis and research describing complete data to calculate the effect size (ES) value. Data analysis in this study is quantitative analysis by calculating the effect size value of each study with the help of OpenMEE software. The results concluded that the ICT-based inquiry-based learning model had a positive effect on students' critical thinking skills with an ES value = 0.839; z= 6.024; < 0.001 This finding provides important information for educators in implementing ICT-based inquiry-based learning model in learning.